MOTIVASI MAHASISWA MELAKSANAKAN PERKULIAHAN OFFLINE STUDI PADA MAHASISWA SOSIOLOGI FISIP UNIVERSITAS RIAU - Adib Rafiqi; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at the Faculty of Social and Political Sciences, Riau University, Pekanbaru City. The purpose of this study is to find out: 1) what is the motivation of sociology students of Fisip Universitas Riau for offline lectures, 2) how to adapt students of sociology Fisip Universitas Riau to offline lectures. This research uses a descriptive Quantitative method. Data collection techniques in this study are observations, questionnaires, and documentation. This study used simple random sampling, where there were 83 respondents. The data analysis technique in this study is descriptive quantitative using SPSS version 23. The results of the research on the motivation of students to carry out offline lectures can be seen that because of the need for achievement, because each individual wants to excel in any case. There is a need for power, because it is man's greatest desire for power, and the need for affiliation, because human beings social beings need to make friends, interact and socialize. The results of student adaptation research carrying out offline lectures can be seen that there are 4 phases of cultural shock in cultural adaptation, namely the honeymoon phase where a person experiences excitement as an initial reaction to an admiration, full of enthusiasm for new things, enthusiastic, friendly, and has a good relationship with the surrounding population. A frustrating phase, phase in which the attraction of new things of a person slowly begins to turn into a sense of frustration. Phase of readjustment the phase in which a person begins to resolve the crisis experienced in the frustrating phase. The resolution phase of the last path that a person takes as a way out of the discomfort he feels. Keywords: Motivation, Adaptation, Offline lectures